The Effect of Principal's Leadership and School Culture on Teachers' Performance - Totok Sasongko; Suyitno Suyitno (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The purpose of this study was to calculate and analyze the effect of the principal's leadership variables and school culture on the teachers'  motivation at Tulungagung Regency. Research methods used in this study included an explanatory quantitative design and data collection techniques made use of a questionnaire that had previously been tested for its validity and reliability with 120 respondents as the sample. A multiple linear regression test is then conducted with the help of SPSS version 17.0 to analyze the collected data. The results show that (1) Descriptively, teacher work motivation was in the good category, principal leadership and school culture were both in the good category. (2) 37.1% of teachers cited the principal's leadership as a significant influence on their motivation to work, (3) School culture has a significant positive impact on teacher work motivation by 56.8%, (4) The principal leadership and school culture together have a significant and positive influence on teacher work motivation of 52.4%. (5) Principal leadership dominates the two independent variables determining teachers' motivation to work.